1995
DOI: 10.1152/ajpgi.1995.268.1.g171
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sex steroid hormones on gastric emptying and gastrointestinal transit in rats

Abstract: In vitro studies have shown that estrogen and progesterone can affect the contractile response and myoelectric activity of the gastrointestinal smooth muscle. The present study was designed to investigate the effect of sex steroid hormones on gastric emptying and gastrointestinal transit were assessed in rats 15 min after intragastric instillation of a test meal containing charcoal and 51Cr. Gastric emptying was determined by measuring the amount of labeled chromium contained in the small intestine as a percen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
97
1
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(107 citation statements)
references
References 0 publications
8
97
1
1
Order By: Relevance
“…Steroids, especially P and E, participate the regulation of gastrointestinal motility [3][4][5] and are involved in the pathogenesis of some functional disorders in the gut [6] . We reported that administration of estrogen inhibited the rat gastric emptying and intestinal transit while P enhanced the gut motility [7] . The effects of E were testified by other scholars while the inhibitory effect of P was observed [8] .…”
Section: Introductionmentioning
confidence: 94%
“…Steroids, especially P and E, participate the regulation of gastrointestinal motility [3][4][5] and are involved in the pathogenesis of some functional disorders in the gut [6] . We reported that administration of estrogen inhibited the rat gastric emptying and intestinal transit while P enhanced the gut motility [7] . The effects of E were testified by other scholars while the inhibitory effect of P was observed [8] .…”
Section: Introductionmentioning
confidence: 94%
“…Estradiol (E 2 ) treatment inhibits gastric emptying in Ovx rats (Wu et al 2002(Wu et al , 2008. This study also demonstrated that E 2 and a combination of E 2 and progesterone inhibit gastric emptying, but progesterone alone enhances gastric emptying in Ovx rats (Chen et al 1995). Furthermore, in male rats, low-dose progesterone has been reported to increase gastric emptying, while high-dose progesterone inhibits it (Liu et al 2002).…”
Section: Discussionmentioning
confidence: 67%
“…Disturbed gastrointestinal transit, leading to a delay in gastric emptying time, is one of the most common phenomenon in pregnant women (Chiloiro et al 2001), and this effect is probably caused by changes in plasma concentrations of certain hormones, such as estrogen (Chen et al 1995) and progesterone (Sheen-Chen et al 2001), as concentrations of these hormones increase throughout pregnancy. Pregnant women with decreased gastrointestinal transit suffer from nausea, vomiting, or abdominal distension during the course of pregnancy, especially during the first trimester (JarnfeltSamsioe et al 1983).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a resting tension of 2 g was applied to the tissues. Electrical field stimulation was then used to define submaximal contraction, carried out at various frequencies (2,4,8,16, 32 and 64 Hz) and voltage (10, 20, 30 and 40 voltage). In order to determine endogenous NO activity, L-arginine (10 -5 M) (Sigma, Cat # A5131) was added to the Krebs' solution.…”
Section: Recording Of Isometric Intestine Contractilitymentioning
confidence: 99%
“…Estrogens are capable to increase the contraction of uterine smooth muscle [3] however, they produce relaxation in smooth muscles of bile duct [4] , trachea [5] and blood vessels [6] . Intestinal motility in human [7] and animals [8] are closely associated with estrous cycle, pregnancy and menopause. It has been demonstrated that changes in concentration of estrogen and progesteron as well as local hormones of digestive tract affects electromechanical behaviour of smooth muscles of gastro-intestinal (GI) tract [9] .…”
Section: Introductionmentioning
confidence: 99%